Ativadores alcalinos e a taipa de pilão: aplicação em solo arenoso - Latosinski, Karina Trevisan (2025)
Earth construction techniques have been used since the earliest civilizations and have gradually undergone transformations, adapting to the binder materials available and the requirements of contemporary buildings. Thus, the use of Portland cement has become widespread for the stabilization of rammed earth walls, which are molded in compacted layers inside formworks that are later removed. Due to the high carbon footprint of Portland cement resulting from its manufacturing process, strategies are needed to reduce its consumption in civil construction. In this context, several studies have explored alkaline activators as an alternative for the production of binders in combination with precursors characterized as sources of aluminum and silicon, often residues or calcined by-products with predominantly amorphous characteristics. There are few studies in the literature that use soil alone as a source of aluminosilicates for alkaline activation, especially in compacted construction applications such as rammed earth. This study aimed to evaluate the effect of alkaline activators on sandy soil from the Campo Grande region (Mato Grosso do Sul, Brazil), with the objective of assessing its suitability for application in rammed earth walls. The methodology was divided into two stages. In the first stage, various mixtures of soil, blast furnace slag, and alkaline activators (sodium hydroxide and hydrated lime), either individually or combined, were tested for compressive strength under ambient curing. In the second stage, new samples were prepared to assess the effect of thermal curing on compressive strength and microstructure (XRD, FTIR, SEM), in addition to monitoring water absorption, drip erosion, and efflorescence formation. The main results showed that samples containing only soil and sodium hydroxide solution formed N-A-S-H cementitious gels, yielding mechanical strength, texture, and workability consistent with regulatory requirements for rammed earth application. Furthermore, mixtures combining both activators (sodium hydroxide and hydrated lime) achieved much higher compressive strengths, also demonstrating feasibility for application. In the evaluation of absorption and erosion, all compositions studied in the second stage presented results consistent with standards. Regarding efflorescence, its occurrence in wrapped samples was negligible compared with unwrapped samples in the first stage. Therefore, this research identified the potential use of alkaline activators (hydrated lime and sodium hydroxide) at concentrations of 1–3% relative to the mass of sandy soil, both individually and combined, under laboratory conditions and optimized proportions, contributing to new solutions applicable to rammed earth construction.